MENINGKATKAN HASIL BELAJAR IPA PADA MATERI GAYA DAN MAGNET MELALUI METODE EKSPERIMEN SISWA KELAS VI C SDN 6 KENDARI - Uddin Uddin (Jurnal Sultra Elementary School, 2020)
The aim of this research is to improve learning outcomes of Natural Sciences on magnetic force material through the experimental method of grade VI.C students. State Elementary School 6 Kendari. This type of research is Classroom Action Research (CAR), a distinctive characteristic of Classroom Action Research (CAR) is the existence of certain actions or actions that aim to improve the learning process in the classroom. The subjects in this study were all students of grade VIC. Kendari 6 Public Elementary School, which consists of 26 students consisting of 11 boys and 15 girls. Types of data: quantitative data obtained from learning outcomes tests and qualitative data obtained through observation sheets. The method of data collection is the data of the situation of the implementation of learning with the experimental method taken using an observation sheet. Data about students' learning outcomes in Natural Sciences is taken using the learning outcomes test tes.Keyword : Activities, Learning Outcomes, Experiments MethodTujuan yang dicapai dalam penelitian ini adalah untuk meningkatkan hasil belajar Ilmu Pengetahuan Alam pada materi  gaya magnet melalui metode eksperimen siswa  kelas VI.C. Sekolah Dasar  Negeri 6 Kendari. Jenis penelitian ini adalah Penelitian Tindakan Kelas (PTK), karakteristik khas dari Penelitian Tindakan Kelas (PTK) adalah adanya tindakan atau aksi tertentu yang bertujuan untuk memperbaiki proses pembelajaran di kelas. Subjek dalam penelitian ini adalah semua siswa kelas VI.C. Sekolah Dasar Negeri 6 Kendari yang berjumlah 26  orang yang terdiri dari 11 orang laki-laki dan 15  orang perempuan. Jenis data: data kuantitatif yang diperoleh dari tes hasil belajar dan data   kualitatif yang diperoleh melalui lembar observasi. Cara pengumpulan data adalah data situasi pelaksanaan pembelajaran dengan metode eksperimen   diambil dengan menggunakan lembar observasi. Data tentang hasil belajar Ilmu Pengetahuan Alam siswa diambil dengan menggunakan tes hasil belajar.Kata Kunci : Aktivitas, Hasil Belajar, Metode Eksperimen